AVALIAÇÃO DO PROCESSO DE TRABALHO DE CIRURGIÕES-DENTISTAS NA ATENÇÃO PRIMÁRIA EM TEMPO DE PANDEMIA DA COVID-19 - Schmidt, Sandra de Vasconcellos (2021)
Introduction: The COVID-19 pandemic caused by the SARS-CoV-2 has brought a high occupational risk to dental surgeons, both due to the characteristic of transmissibility and the peculiarity of the proximity of the dental surgeon to the patient in clinical